Investigating the Relationship between Weaknesses in Internal Control and Abnormal Production Costs of Companies Listed in Tehran Stock Exchange - Jafar Maboudi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Part of the Sarbanes–Oxley Act is to disclose weaknesses in the corporate internal control so that investors can use them to make the right decisions. Similarly, many analysts believe that real profit management can be a criterion for measuring the manipulation of a company's actual activities. Be a company. This study aims to examine the relationship between weakness in internal control and manipulation of the actual activities of companies listed on the Tehran Stock Exchange. In this study, weakness in internal control is an independent variable that is measured based on the model of Leonard et al. and manipulation of the actual activities of the company as a dependent variable that is measured based on Cohen's ministry model. To achieve the goal of this research, 94 companies listed on the Tehran Stock Exchange have been selected as a statistical sample of the research by systematic removal in the period 2010-2015 and they were examined using panel data. The results of this study revealed that there is a negative and significant relationship between weakness in internal control and abnormal production costs.